IDENTIFIKASI BAHAYA, PENILAIAN RISIKO, DAN PENGENDALIAN RISIKO PEKERJAAN PADA AREA PRODUKSI DI PT. LEMBAH KARET PADANG TAHUN 2020 - Friska Eka Fitria (Ensiklopedia of Journal, 2021)
Increased cases of work accidents at PT. Lembah Karet Padang from 2016 to 2018 in production areas that can endanger the safety of workers, it is necessary to identify hazards, risk assessments, and risk control. The purpose of this study was to determine the hazards, risk assessments and risk control of work in the Production Area so as to prevent work accidents. The design of this research is descriptive qualitative. The place of this research is at PT. Lembah Karet Padang. This research was conducted in February-October 2020. The results showed that in the weighing process there were 9 potential hazards with a risk level of Extreme Risk (E) with the potential for slippery floors, risk control using Personal Protective Equipment (PPE). In the milling process there are 15 potential hazards with a risk level of Extreme Risk (E) with the potential for slippery floors, risk control using PPE. In the crushing process, there are 7 potential hazards with a risk level of Extreme Risk (E) with the potential for slippery floors, risk control using PPE. In the lory washing process there are 4 potential hazards with a risk level of High Risk (H) with a potential noise hazard, risk control with Administration Control and wearing ear plugs. In the press process there are 7 potential hazards with a high risk level (H) with the potential for large knives, noise, forklift engines, and dust. Risk control in this process by wearing PPE and making forklift paths. It is expected that the company will identify hazards, assess risks and carry out periodic control and monitoring of the workers.